German-Chinese economic relations: Opportunities and risks - Georg Erber (DIW Economic Bulletin, 2012)
Economic relations between Germany and China have developed exceptionally well over the past few decades. China has grown to become one of Germany's key trading partners and may even become the second-largest trading partner after France in the coming year. And yet China's focus is increasingly shifting towards capital goods manufacturing, meaning Chinese enterprises will be competing with German enterprises more strongly on global markets. There are more and more indications that the extensive direct and indirect subsidizing of businesses in China is a major contributory factor to cut-throat competition, which is becoming increasingly incompatible with the concept of free trading within the WTO regulatory framework. Recent examples of this can be found, in particular, in the manufacture of wind turbines, photovoltaic installations, and, more recently, even high-speed trains, as well as the exploitation of China's quasi-monopoly on rare earths. In other high-tech sectors, too, the competition is likely to become fiercer. What is needed, therefore, is forward-looking industrial, innovation and trade policy that does not create major distortions of competition in Germany's economic relations with China.
Keywords: F14; F59; L16; 330; Germany; China; economic relations; trade and foreign direct investments